2012
DOI: 10.1002/lary.23229
|View full text |Cite
|
Sign up to set email alerts
|

New technology applications: Knotless barbed suture for tracheal resection anastomosis

Abstract: Tracheal anastomosis with running v-loc suture is a feasible alternative to conventional closure with interrupted Vicryl suture. V-loc suture provided a surgical advantage by improved ease of use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 42 publications
(109 reference statements)
2
21
1
Order By: Relevance
“…We found that barbed suture repairs had nearly identical load to failure compared with non‐barbed suture repair under our testing conditions, suggesting that barbed suture repair may be a viable alternative for canine diaphragm hernia repair. Our findings are consistent with previous reports of barbed suture use in tracheal anastomosis; tendon repair; gastrotomy and enterotomy closure; and skin closure compared with conventional suture repair. In a canine model, bursting strength (day 3, 7, and 14) of gastrotomy and enterotomy closure with either barbed (3‐0 V‐Loc™ 90 device) or non‐barbed suture (3‐0 Biosyn™ was not different …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that barbed suture repairs had nearly identical load to failure compared with non‐barbed suture repair under our testing conditions, suggesting that barbed suture repair may be a viable alternative for canine diaphragm hernia repair. Our findings are consistent with previous reports of barbed suture use in tracheal anastomosis; tendon repair; gastrotomy and enterotomy closure; and skin closure compared with conventional suture repair. In a canine model, bursting strength (day 3, 7, and 14) of gastrotomy and enterotomy closure with either barbed (3‐0 V‐Loc™ 90 device) or non‐barbed suture (3‐0 Biosyn™ was not different …”
Section: Discussionsupporting
confidence: 92%
“…15,16 Barbed suture material has also been used experimentally for closure of jejunal and colonic enterotomy, gastrotomy, incisional gastropexy, tracheal resection and anastomosis, and abdominal wall closure, with similar success to conventional suture material. [17][18][19][20][21][22][23] When applied to the diaphragm musculature, especially in a compromised patient, barbed suture material could offer an advantage to traditional intracorporeal sutures by eliminating difficult knot tying, enhancing suture line security and, thus, efficiency of the procedure.…”
mentioning
confidence: 99%
“…Developing the ideal tracheal graft requires matching the mechanical properties of the graft to that of the native trachea . Previous studies have been conducted investigating properties of human, porcine, rabbit, sheep, rat, and canine trachea . Inconsistency in methods and parameters measured makes comparison among these various studies difficult.…”
Section: Discussionmentioning
confidence: 99%
“…2 Previous studies have been conducted investigating properties of human, porcine, rabbit, sheep, rat, and canine trachea. [16][17][18][19][20][21][22][23][24][25] Inconsistency in methods and parameters measured makes comparison among these various studies difficult. We found the maximum load of the rabbit trachea to be 6 N. This is in comparison to studies on rat trachea demonstrating 3.5 N and sheep trachea at 198 N. 13,21 It may be inferred that the larger trachea of the sheep allows for increased strength, but with caution as each study was conducted in a different setting with variables that cannot be isolated.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The middle turbinate is surgically medialized at the beginning of the case by dividing the second portion of the basal lamella, most commonly with a Cottle elevator. This is accomplished through the use of a monofilament barbed suture placed through both middle turbinates and the nasal septum.…”
Section: Techniquementioning
confidence: 99%